2012
DOI: 10.5455/jeim.070512.or.029
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal interaction during the acute phase of experimental <i>Trypanosoma cruzi</i> infection: the influence of aldosterone and the AT1 receptor on mortality

Abstract: Introduction: Trypanosoma cruzi infection is a serious public health problem in Latin America. Despite positive results from programs directed to the interruption of vectorial transmission, there are still millions of people infected, and a large number, at the risk of infection. Chagas disease is typically associated with cardiac complications, and chronic symptoms include heart failure and megaesophagus development. Objective: In this study, we aimed to evaluate the importance of the cardiorenal axis and ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Most studies indicated that RAS-modulating drugs were effective in reducing parasitaemia (Chumbinho et al ., 2012; Leite et al ., 2017) and mortality (de Paula Costa et al ., 2010; Chumbinho et al ., 2012; Penitente et al ., 2015). Conversely, parasitaemia was unchanged by enalapril (Penitente et al ., 2015), while high doses of captopril (75 mg L −1 ) increased the animals’ mortality with no impact on heart parasitism (Leon et al ., 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies indicated that RAS-modulating drugs were effective in reducing parasitaemia (Chumbinho et al ., 2012; Leite et al ., 2017) and mortality (de Paula Costa et al ., 2010; Chumbinho et al ., 2012; Penitente et al ., 2015). Conversely, parasitaemia was unchanged by enalapril (Penitente et al ., 2015), while high doses of captopril (75 mg L −1 ) increased the animals’ mortality with no impact on heart parasitism (Leon et al ., 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Only Chumbinho et al . (2012) analysed biochemical markers of organ toxicity (i.e. serum creatinine and urea), indicating that losartan increased kidney injury in T. cruzi -infected mice (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chumbinho et al (2012) also described that the mortality rate in T. cruzi infected mice was under the direct influence of aldosterone. According to the same authors, aldosterone blockage with spironolactone (an aldosterone antagonist) attenuates the parasite load and reduces the severity of Chagas cardiomyopathy [ 49 ]. Currently is also known that a prolonged aldosterone treatment (between 4 and 5 weeks) triggers enhanced oxidative stress production and accounts for a proinflammatory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of functional and structural kidney abnormalities after T. cruzi infection, associated with reduction in renal blood flow, proximal tubular damage, and inflammatory interstitial infiltrate. An observation is made of an increased production of pro-inflammatory cytokines and nitric oxide, as well as renal function loss associated with high parasitic load [9][10][11][12]. In the acute phase, the renal lesion is related to cardiovascular dysfunction, due to a transitory decrease in renal blood flow, which was demonstrated in experimental models [11,13].…”
Section: Chagas Diseasementioning
confidence: 99%